2014
DOI: 10.1603/ec13377
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Potato Resistance to <I>Euscepes postfasciatus</I> (Coleoptera: Curculionidae): Larval Performance Adversely Effected by Adult's Preference to Tuber for Food and Oviposition

Abstract: The preferences of the West Indian sweet potato weevil, Euscepes postfasciatus (Fairmaire), to tubers of sweet potato, Ipomoea batatas (L.), for food and for oviposition were evaluated, and correlated to sweet potato's resistance to immatures. Adults (parent) were released in a plastic box containing tubers of sweet potato cultivars and maintained for 5 d, after which the adults on each tuber were counted. All adults were then removed and each tuber was maintained separately. New adults that emerged from the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Even if adults prefer a given cultivar for food and oviposition, the pest cannot increase rapidly unless the quality of the storage root also provides for larval development. Sweetpotato resistance to weevils has been reported in the laboratory and field (e.g., Blank et al 2001 , Bottega et al 2010 , França and Ritschel 2002 , Okada et al 2014 , 2015 , Silva and Ritschel 2001 , Wanderley et al 2004 ). However, few studies have considered the preference of weevil adults for certain cultivars and the suitability of the preferred cultivars for the juvenile development.…”
Section: Weevilsmentioning
confidence: 99%
“…Even if adults prefer a given cultivar for food and oviposition, the pest cannot increase rapidly unless the quality of the storage root also provides for larval development. Sweetpotato resistance to weevils has been reported in the laboratory and field (e.g., Blank et al 2001 , Bottega et al 2010 , França and Ritschel 2002 , Okada et al 2014 , 2015 , Silva and Ritschel 2001 , Wanderley et al 2004 ). However, few studies have considered the preference of weevil adults for certain cultivars and the suitability of the preferred cultivars for the juvenile development.…”
Section: Weevilsmentioning
confidence: 99%
“…Different subspecies of the pest occur in different areas of the world; however, their mode of infestation is almost the same (Capinera 2001). As cited by Okada et al (2014), the weevils have distinct modes of damage such that physical injury is inflicted when the weevils feed, therefore creating problems on the surface and flesh. Liao et al (2020) reported that tuber infestation of sweet potato weevils results in the induced production of secondary metabolites that eventually reduce tuber quality and marketability.…”
Section: Introductionmentioning
confidence: 99%
“…Sweet potato genotypes show resistance to pests like Diabrotica spp. (Jackson and Bohac, 2007), Chaetocnema confinis Crotch (Abney and Kennedy, 2011) (Coleoptera: Chrysomelidae), and the root borer, Euscepes postfasciatus (Coleoptera: Curculionidae) (Okada et al, 2014).…”
Section: Introductionmentioning
confidence: 99%